Aerodynamics of ribbed bicycle racing helmets - Alam, F.; Chowdhury, H.; Wei, H. Z.; Mustary, I.; Zimmer, G. (Procedia Engineering, 2014)
In competitive cycling, aero-helmets have been used around since 1980 to reduce aerodynamic resistance. Considerable design effort has been made to improve the aerodynamic efficiency of racing bicycle helmets over the years. However, the demand for further improvement has forced helmet manufacturers and designers to introduce new designs progressively. Recently several helmet manufacturers (e.g., LG, Lazer and Giro) have introduced dimples on the outer shell of helmet mimicking the so called `Golf-ball` dimple effects with a view to further reduce aerodynamic drag of the helmet. However, no independently verifiable research so far has been reported in the public domain about the aerodynamic performance of ribbed bicycle helmets compared to smooth surfaced helmets. Hence, the primary objective of this work was to undertake an experimental study on four smooth aero-helmets including two latest model ribbed aero-helmets to understand their aerodynamic performance and the effect of dimples on helmets. The investigation was undertaken in an wind tunnel environment over a range of wind speeds, pitch and yaw angles. The experimental data indicate no measurable advantage between the smooth and ribbed helmets under varied pitch angles and at zero yaw angle.